Solvency II, Undertaking Specific Parameters (USPs) Validation, Generalization and Criticism (Contemporary Mathematics, 2021)
This paper provides a deeper actuarial insight in the mathematics and algorithms described in Delegate Act 35/2015 of Solvency II legislative framework with respect to the determination of Undertaking Specific Parameters (USPs). The numerical investigation is based on typical input signals used by control engineers in order to check the system response. It is finally revealed the close relationship between the USPs values and the values of the typical function of standard deviation. Finally, a generalization of the mathematical framework covering the special cases of the Pareto and Gamma distributions as inputs for the aggregate losses of an insurance company is provided.
Keywords: Solvency II, Standard Formula (SF), Undertaking Specific Parameters (USPs), Maximum likelihood, Control engineering, Spike-Ramp-Step signals